Charting the future of public service exploring career development expectations among generation Z employees in national government agencies in Eastern Visayas - Alberto, Norielle Val M.; Anagap, Kristia S.; Brazil, Alexis Edmon N.; Elvas, Angelica A.
The Generation Z, encompassing individuals with birth years falling between 1995 and 2015, is currently making its way into the labor force. Thus, it is important to determine the career development expectations of Generation Z working in National Government Agencies also to analyze the current Human Resource Policies of their respective agencies in terms of their alignment with each other, using a Convergent Parallel Mixed Methodology. The quantitative research method employed a Likert Scale Questionnaire and distributed to 173 respondents using convenient sampling. Afterwards, the mean and frequency values were calculated for analysis. The questions were categorized into three categories namely: (1) Skills Development and Personal Growth Factors, (2) Career Mobility and Advancement Factors, and (3) Human Resource Planning and Preparedness Factors. Based on the results, all categories are valued by Generation Z, however, they are leaning most on valuing the Career Mobility and Advancement Factors. Meanwhile, in terms of individual ranking, almost all of the respondents valued growing as a person in their career and learning new skills at work the most. Contrastingly, it was common among the respondents that they least valued the provision of challenging workloads and valuing the opportunities for personal and professional career development as compared to earning a large salary. The qualitative research method interviewed four key informants who are involved in HR planning in their respective agencies. Three themes emerged from the responses of the respondents namely perspectives, policies, and plans. The exploration of these perspectives and the identification of Generation Z's career development expectations unveiled the existing gap between the two variables that negatively affects the future of the public sector if left unresolved.